International Migration of High-Level Manpower from Developing to Developed - TOBOL, ABULKASEM (Dirasat in Economics and Business, 1981)
The developing countries are both importers and exporters of high level manpower. However, many developing countries are experiencing what is called "Brain Drain". The term Brain Drain means the out migration of the high level manpower. The high level manpower may constitute a tiny fraction of the labor force but its role in the development of the country is crucial. l This study concentrates on the permanent movement of highly trained people from the less developed countries to developed countries. It does not deal with all movements of people around the world.